Sex Differences in Cardiac Function After Prolonged Strenuous Exercise. Issue 3 (May 2015) - Cote, Anita T.; Phillips, Aaron A.; Foulds, Heather J.; Charlesworth, Sarah A.; Bredin, Shannon S.D.; Burr, Jamie F.; Koehle, Michael S.; Warburton, Darren E.R.
Abstract : Objective: To evaluate sex differences in left ventricular (LV) function after an ultramarathon, and the association of vascular and training indices with the magnitude of exercise-induced cardiac fatigue. Design: Descriptive field study. Setting: Fat Dog 100 Ultramarathon Trail Race, Canada. Participants: Thirty-four (13 women) recreational runners (aged 28-56 years). Interventions: A 100-km or 160-km mountain marathon. Main Outcome Measures: Baseline baroreceptor sensitivity, heart rate variability, and arterial compliance; Pre-exercise and postexercise echocardiographic evaluations of LV dimensions, volumes, Doppler flow velocities, tissue velocities, strain, and strain rate. Results: Finishers represented 17 men (44.8 ± 6.6 years) and 8 women (45.9 ± 10.2 years; P = 0.758). After ultraendurance exercise, significant reductions ( P < 0.05) in fractional shortening (men: 40.9 ± 6.9 to 34.1 ± 7.6%; women: 42.5 ± 6.5 to 34.6 ± 7.9%) diastolic filling (E/A, men: 1.28 ± 0.68 to 1.26 ± 0.33; women: 1.55 ± 0.51 to 1.30 ± 0.27), septal and lateral tissue velocities (E′), and longitudinal strain (men: −21.02 ± 1.98 to −18.44 ± 0.34; women: −20.28 ± 1.90 to −18.44 ± 2.34) were observed. Sex differences were found for baseline cardiac structure and global function, peak late transmitral flow velocity, and estimates of LV filling pressures ( P < 0.05). Regression analysis found that higher baseline arterial compliance was associated with lower reductions in cardiac function postexercise, to which sex was a significant factor for E′ of the lateral wall. Faster race pace and greater lifetime ultramarathons were associated with lower reductions in LV longitudinal strain ( P < 0.05). Conclusions: Cardiac responses after an ultramarathon were similar between men and women. Greater evidence of exercise-induced cardiac fatigue was found to be associated with lower baseline arterial compliance and training status/experience. Clinical Relevance: These findings suggest that vascular health is an important contributor to the degree of cardiovascular strain incurred as the result of an acute bout of prolonged strenuous exercise.